2015
DOI: 10.17126/joralres.2015.072
|View full text |Cite
|
Sign up to set email alerts
|

Measuring color change of tooth enamel by in vitro remineralization of white spot lesion.

Abstract: Objective colour determination is based on calculating the colorimetric distance (ΔE) within a colour space. So far, the most used colour space in dentistry is CIE L*a*b (Comission Internationale de l´Éclairage). CIE L*C*h* has been recently developed, showing a better correlation with the perception of the human eye. Objective: To determine the ability of an in vitro remineralisation substance to blend the colour of white spot lesions (WSL) with sound enamel, determining ΔE by using the CIE L*C*h* colour spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…37 Therefore, higher color change values and increased darkness upon staining. 31 Samples immersed in artificial saliva showed color change values higher than both CPP-ACP and resin infiltration. One possible explanation is that artificial saliva resulted only in deposition of minerals on the surface layer leaving the body of the lesion demineralized.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…37 Therefore, higher color change values and increased darkness upon staining. 31 Samples immersed in artificial saliva showed color change values higher than both CPP-ACP and resin infiltration. One possible explanation is that artificial saliva resulted only in deposition of minerals on the surface layer leaving the body of the lesion demineralized.…”
Section: Discussionmentioning
confidence: 91%
“…White spot lesions (WSLs) are early signs of demineralization process resulting in chalky white appearance of the enamel surface. 31 Several ways have been proposed for treatment of WSLs. However, some socially consumed beverages, such as coffee, Coca-Cola and tea may result in discoloration of the WSLs even after treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed statistically significant differences in ∆E3 between the ACP groups and the saliva group. Tolcachir et al [ 17 ] found that CPP-ACP penetrated to the depth of the WSL and turned its appearance similar to that of the sound enamel. In their study, CPP-ACP caused a noticeable change in color of WSLs.…”
Section: Discussionmentioning
confidence: 99%
“…After detecting the opaque white area, an acid etchant of 35% phosphoric acid solution (Ultradent Products Inc., South Jordan, Utah, USA) was applied to the chalky area of the tooth for 30 seconds, which was followed by rinsing with distilled water, and then air-dried. This treatment effectively removed the white opaque layer, exposing the WSLs (8) .…”
Section: Ii2 Creation Of White-spot Lesions (Wsls)mentioning
confidence: 99%